Reassessing Strategic Identity: Academic Perceptions of UIN Sunan Kalijaga’s Vision, Mission, and Objectives - Munthe, Bermawy; Satibi, Ibi (Islamic Education Management Study Program, Faculty of Tarbiyah and Education State Islamic University (UIN) Sunan Kalijaga Yogyakarta, Indonesia, 2024)
Purpose – This study aimed to assess the perceptions of the academic community regarding the relevance, strengths, and weaknesses of the vision, mission, and objectives of Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta and to propose strategic recommendations for their refinement. Design/methods – A qualitative research design was employed, utilizing in-depth interviews with selected faculty leaders, literature studies, and document analysis of institutional records to ensure a comprehensive and triangulated understanding. Data were manually coded and thematically analyzed to identify major patterns and critical areas for improvement. Findings – The findings reveal that UIN Sunan Kalijaga possesses strong institutional pride, iconic status, inclusive and integrative core values, significant academic achievements, and extensive collaborations. However, deficiencies were identified in the clarity, dissemination, and operationalization of its vision and mission, along with a need for greater strategic alignment with contemporary global academic trends. Research implications/limitations – The purposive sampling method and focus on a limited timeframe may affect the generalizability of the findings. Additionally, the qualitative nature of the study limits the scope for broader quantitative validation across the institution's diverse academic population. Practical implications – Strengthening participatory governance in updating the vision and mission, enhancing curriculum relevancy, and reinforcing international collaboration mechanisms are critical steps to positioning UIN Sunan Kalijaga as a globally competitive institution. Originality/value – This research provides one of the first comprehensive qualitative mappings of internal academic perceptions two decades after the formulation of UIN Sunan Kalijaga’s strategic identity, offering empirical recommendations crucial for guiding future institutional development within the global higher education landscape.